Are we doing enough to control infection risk in Australian small animal veterinary practice? Findings from a mixed methods study - Willemsen, Angela; Cobbold, Rowland; Gibson, Justine; Wilks, Kathryn; Reid, Simon (Frontiers in Public Health, 2024)
BackgroundManaging risk effectively within small animal veterinary practice is integral for staff, patient and client safety. Veterinary personnel are exposed to many risks, including bites, scratches, sharps injuries and exposure to zoonotic diseases and multi-resistant organisms. Patients may also be exposed to healthcare-associated infections, including multi-resistant organisms. While veterinary owners/managers have a duty of care under legislated Workplace Health and Safety requirements, all staff have a responsibility to contribute to assessing and minimizing risk. The application of standard and transmission precautions will help with risk minimization. This study aimed to determine how small animal veterinary staff understand and perceive infection prevention and control risk and to provide recommendations to assist with risk mitigation.MethodsA mixed methods design was used. A digital questionnaire was administered to small animal veterinary staff in Australia to identify knowledge, attitudes and practices of risk related behaviors. Follow up focus groups were conducted with small animal practitioners to explore factors supporting and preventing veterinary staff from implementing recommended practices identified in the questionnaire.ResultsSmall animal veterinary staff acknowledged they participated in many high-risk activities, including recapping needles and eating and drinking in patient care areas. Injuries were common, with 77% of staff receiving a bite or scratch, and 22% receiving a sharps injury in the preceding six months. Less than one in five of these incidents was reported. Staff agreed effective infection prevention and control was the responsibility of all staff, but a designated staff member should take responsibility for managing it. The practice owner/manager was integral to supporting and promoting recommended strategies, contributing to a positive workplace culture and improving safety for staff and patients.ConclusionSmall animal veterinary staff have some understanding of how to identify, report, manage and mitigate risk but were limited by their knowledge of infection prevention and control principles.